SIDE EFFECTS OF RAPID WEIGHT LOSS IN ATHLETES - Jalolov Nozimjon Nodir o‘g‘li; Sultonov Erkin Yoqubjon o‘g‘li (American Journals Publishing, 2024)
This article provides detailed information on the effects of rapid weight loss methods on the physical and psychological health of athletes. The negative effects of calorie restriction, dehydration, and pharmacological methods on the body are highlighted based on scientific evidence. Despite the positive short-term results, such approaches can reduce athletic performance and pose serious health risks in the long term.
Keywords: Rapid weight loss, athletes, dehydration, muscle mass loss, healthy eating, sports injuries